Раскрой скобки и упрости выражение:−7(4x+9)−(3+x)+2(9+6x) срочно нужен ответ дам 5 звёзд

0 голосов
26 просмотров

Раскрой скобки и упрости выражение:−7(4x+9)−(3+x)+2(9+6x) срочно нужен ответ дам 5 звёзд


Математика (16 баллов) | 26 просмотров
Дано ответов: 2
0 голосов

Ответ:-28x-63-3+x+18+12x

-28x+x+12=-63-3+18

-15x=-48

X=3,6

Пошаговое объяснение:

(22 баллов)
0

там минус перед скобками. -7(4х+9)-(3+х)+2(9+6х)= -28х-63-3-х+18+12х

0 голосов

Ответ:

Пошаговое объяснение:

−7 * (4x + 9) − (3 + x) + 2 * (9 + 6x) = -28х - 63 - 3 - х + 18 + 12х = -17х - 48

(3.2k баллов)